Effect of local injection of Zolena, zoledronic acid made in Iran, on orthodontic tooth movement and root and bone resorption in rats - Massoud Seifi; Sohrab Asefi; Ghazal Hatamifard; Ali Lotfi (Tabriz University of Medical Sciences, 2017)
Background. Anchorage control is an essential part of orthodontic treatment planning, especially in adult patients who demand a more convenient treatment. Zoledronic acid (ZA) is an effective choice to address this problem. It is the most potent member of the bisphosphonates family that has an inhibitory effect on bone resorption by suppressing osteoclast function. Therefore, ZA might be a good option for orthodontic anchorage control. The current study evaluated the effect of local administration of Zolena (ZA made in Iran) on orthodontic tooth movement (OTM) and root and bone resorption. Methods. The experimental group consisted of 30 rats in 3 subgroups (n=10). Anesthesia was induced, and one closed NiTi coil spring was installed between the first molar and central incisor unilaterally, except for the negative control group. The positive control group received vestibular injection of 0.01 mL of saline next to the maxillary first molar, and 0.01 mL of the solution was injected at the same site in the ZA group. After 21 days, the rats were sacrificed and the distance between the first and second molars was measured with a leaf gauge. Histological analysis was conducted by a blind pathologist for the number of Howship's lacunae, blood vessels, osteoclast-like cells and root resorption lacunae. Data were analyzed with ANOVA, Tukey test and t-test. Results. There were no significant differences in OTM between the force-applied groups. ZA significantly inhibited bone/root resorption and angiogenesis compared to the positive control group. Conclusion. Zolena did not decrease OTM but significantly inhibited bone and root resorption. Zolena might be less potent than its foreign counterparts.